“SAB’AI SAYYOR” DOSTONI TARJIMASIDA MUQOBIL SO‘Z VA BADIIY USLUB - Azilova, Z.G. (SCIENCE and SOCIETY, 2025)
This article explores the issue of equivalent words and artistic style in the Karakalpak translation of Alisher Navoi's epic “Sab’ai Sayyor”, providing a comparative analysis with the original text. Additionally, the couplets from the original and the translation are compared to highlight their semantic correspondence.
Keywords: original; translation; content; continuity; synonymous expression